Disruptive Innovation and the Idea of Technology - Cressman, Darryl (NOvation — Critical Studies of Innovation, 2019)
From its obscure origins in management theory, disruptive innovation has become one of the concepts used to describe how networked digital technologies and platforms transform industries and institutions. In this paper, I will examine how contested, and at times incommensurable, iterations of disruptive innovation share a similar idea of technology. Drawing upon discourses of disruptive innovation from management theory, institutional policies, and popular culture reveals a shared idea of technology whose characteristics include a reified idea of technology and a horizon of expectations in which fear of falling behind influences ideas about technological change.